Gender and Age-responsive Social Protection - United Nations Women (2019)
Adolescence is recognized as a window of opportunity for offsetting childhood disadvantage and altering life trajectories. With more than one billion adolescents in the world, and many countries in the Global South experiencing a youth bulge, there is increasing urgency for national governments and donors to provide greater support, services and programming to this age group. Evidence on the economic and social impacts of cash transfers (CTs) highlights that such programmes can reap multiple dividends across the lifecycle—including in terms of school and health service uptake, intra-household decision-making and intimate partner violence. There is growing interest in how to leverage these programmes to improve adolescent well-being across the second decade of life and beyond. This policy brief reviews the effects of CTs on the rights and capabilities of adolescent girls and boys (10–19 years) using a gender and capability lens and focusing on three key capability domains: education; sexual and reproductive health; and freedom from violence. Based on this evidence, the brief highlights the importance of a ‘cash plus’ approach to enhancing adolescents’ multi-dimensional well-being and achieving the 2030 Agenda for Sustainable Development.